Suicide, Associated factors and Psycho Social Impact – Evidence from the literature - Menaka, S.; Sivakaran, N. (My University, 2017)
The objective of this study is a review of existing body of suicide research, statistics and summarizes the research on the impact of suicide on individuals within families, society and social networks and a ‘model’ is produced to explain the path way of suicide and associated factors of suicide and behavior patterns of person who committed or attempted suicide. The methodology of this study was drawn upon theory and practice in order to explain how suicide created disadvantaged in socioeconomic positions in a family, society, and the development of the nation.
Keywords: Suicide; Associated factors; Psychological impact; Social impact; Economical impact